Ocular Ailments Doctrine (Ophthalmology) in Fish: Exophthalmia Scenario as Forzando and Eyes - Brain Connection - Filik, N (Journal of the Hellenic Veterinary Medical Society, 2025)
Ocular ailments are leading cause of fish vision loss in worldwide. Eye is an island of soft tissue surrounded by neural crest derived tissues of craniofacial skeleton. Eye tissue is extraordinary organ in terms of its development. The visual pathway consist of retina, optic nerves, optic chiasm, optic tracts, lateral geniculate bodies, optic radiations, and visual cortex. The pathway is, effectively, part of the central nervous system. Events such as oedema, bleeding, aneurysm (vessel ballooning) that will develop behind the eyeballs may also cause exophthalmia, that is, protrusion of the eyeballs. A decrease in strength or paralysis that will develop in the muscles that move the eye can also be counted among the factors that will cause Exophthalmia ailment is manifestations of an abnormal protrusion of ocular globe beyond confines of bony orbit. Eye disease primarily affects the cornea. Eyes inflammatories; Parasitic infestation, Mycobacterial infection, Periocular cellulitis/dermatitis, Panophthalmitis, Endophthalmitis, Iridovirus, Septicaemia, Keratitis, Cataract, Uveitis, Choroiditis, Scleritis, Periocular steatitis, Encephalitis, Extraocular myositis, Keratoconjunctivitis, Meningitis, Optic neuritis. Whichever the case, the injury likely triggered an immune system response. This case is what causes oedema. Sick fish other ailments experience exophthalmia. For example, visceral organs failure, kidney failure, tummy cavity disease, or vital dangerous metabolic diseases can cause fluid buildup. Ailment can lead to dry or gritty eyes, redness, puffy eyes inflammation and swelling vision problems. This review manuscript aim is to talk about doctrine of ophthalmology, to explain situations in which eye, structures around eye and visual system are affected by a series of clinical events, to present a case report of exophthalmia eye disorder, to emphasize relationship between eye and brain, to briefly explain diagnosis and treatment of such conditions together with ophthalmology and microsurgery, and to present disease setting in a polemically way.